A case of an alpha-fetoprotein-producing gastric so-called carcinosarcoma with enteroblastic differentiation - Shiori Meguro; Daisuke Suzuki; Toru Kawai; Takanori Kyokane; Yoichiro Aoshima; Yasunori Enomoto; Haruna Yagi; Hideya Kawasaki; Isao Kosugi; Hiroe Tsukui; Satoshi Baba; Toshihide Iwashita (Elsevier, 2020)
We present an extremely rare case of an alpha-fetoprotein (AFP)-producing gastric so-called carcinosarcoma with enteroblastic differentiation in a 74-year old man. After detecting a type 1 (polypoid) tumor (40 × 35 mm) in the upper stomach, the patient underwent total gastrectomy and lymphadenectomy. Microscopically, the tumor comprised a fetal gut-like adenocarcinoma component, common tubular adenocarcinoma component, and sarcomatous component. The fetal gut-like adenocarcinoma component was positive for AFP, GPC3, SALL4, and CLDN6, whereas the common tubular adenocarcinoma component was positive for SALL4, but negative for AFP, GPC3, and CLDN6. The sarcomatous component was composed of atypical spindle cells and was negative for AE1/3, AFP, and CLDN6, but part of the sarcomatous component was positive for SALL4 and GPC3. Multiple liver metastases appeared, and the patient died fifteen months after the surgery. To our knowledge, this is the first report describing the immunohistochemical characteristics of gastric carcinosarcoma with enteroblastic differentiation.